Surgical safe zones for oblique lumbar interbody fusion of L1‐5: A cadaveric study. Issue 2 (18th November 2021) - Deng, Donghai; Liao, Xuqiang; Wu, Ruihui; Zhou, Yunfei; Huang, Xingqiu; Shi, Chenglong; Shi, Benchao; Min, Shaoxiong
Abstract: To evaluate the operating range and morphology of the surgical safe zone for oblique lumbar interbody fusion (OLIF). Twenty embalmed full‐torso cadaveric specimens were dissected. The oblique corridor and the distance between adjacent lumbar arteries were measured in a static state and with psoas major retraction. The morphology and size of the safe zone for OLIF and the location of the lumbar sympathetic trunk were also recorded. The oblique corridor of the L1‐L5 segments was significantly greater in the retracted state than in the static state ( p  < 0.05). With psoas major retraction, the distances between adjacent lumbar arteries at L1‐4 were significantly greater ( p  < 0.05) than those in the static state. The lumbar sympathetic trunk is just located in the safe zone and travels downward adjacent to the psoas major. The shape of the safe zone for OLIF was approximately an oblique upward parallelogram at L1/2 and L2/3, an isosceles trapezoid at L3/4, and an irregular quadrangle or triangle at L4/5. The safe zone for OLIF at L1/2, L2/3, and L3/4 was significantly larger during retraction than in the static state ( p  < 0.05). On the lateral side of the lumbar spine there is a natural surgical safe zone for OLIF, which can provide a sufficient operating space. The safe zone has a certain morphological pattern in L1‐5 segments and psoas major retraction can significantly enlarge it.